2017
DOI: 10.1021/acs.nanolett.7b03358
|View full text |Cite
|
Sign up to set email alerts
|

The role of Vimentin in Regulating Cell Invasive Migration in Dense Cultures of Breast Carcinoma Cells

Abstract: Cell migration and mechanics are tightly regulated by the integrated activities of the various cytoskeletal networks. In cancer cells, cytoskeletal modulations have been implicated in the loss of tissue integrity and acquisition of an invasive phenotype. In epithelial cancers, for example, increased expression of the cytoskeletal filament protein vimentin correlates with metastatic potential. Nonetheless, the exact mechanism whereby vimentin affects cell motility remains poorly understood. In this study, we me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 52 publications
10
62
1
Order By: Relevance
“…Figure 2F showed a decrease in YAP upon HIC1 overexpression and an increase in it upon HIC1 knockdown. 35 The expression of E-cadherin and ZO-1 was found significantly increased in the HIC1-overexpressed group but decreased in the HIC1knockdown group; the opposite was found for the expression of N-cadherin and vimentin ( Figure 3C). The migratory and invasive ability was examined by the means of wound healing ( Figure 3A) and transwell migration assay ( Figure 3B), respectively.…”
Section: Hic1 Inhibits the Proliferation Of Bcamentioning
confidence: 85%
“…Figure 2F showed a decrease in YAP upon HIC1 overexpression and an increase in it upon HIC1 knockdown. 35 The expression of E-cadherin and ZO-1 was found significantly increased in the HIC1-overexpressed group but decreased in the HIC1knockdown group; the opposite was found for the expression of N-cadherin and vimentin ( Figure 3C). The migratory and invasive ability was examined by the means of wound healing ( Figure 3A) and transwell migration assay ( Figure 3B), respectively.…”
Section: Hic1 Inhibits the Proliferation Of Bcamentioning
confidence: 85%
“…Simultaneously, vimentin itself has a role in modulating EMT signaling. Vimentin levels seem to regulate Snail expression in a feedback loop, and a knock-down of vimentin resulted in decreased Snail1 mRNA levels [12]. Over-expression of vimentin leads to an increase in Slug expression levels, while down-regulation has the opposite effect [10].…”
Section: Vimentin In Emtmentioning
confidence: 99%
“…Over-expression of vimentin in epithelial cells has been shown to be sufficient for cells to adopt the elongated shape typical of mesenchymal cells. This is followed by the reorganization of the actin and microtubule cytoskeletons [10], the internalization of desmosomes [11], and the rearrangement of keratin IFs [12]. Conversely, downregulation of vimentin not only hampers the migration of a large variety of tumor cell lines [4] but also partially restores their epithelial phenotype [13].EMT is governed by several signaling pathways that exhibit complex interactions with vimentin, as demonstrated in numerous studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that vimentin deprived cells are less mechanically stable and migrate more slowly [5], whereas cells lacking keratin are softer and more deformable [6,7]. These differences are likely to play an important role during endothelial-tomesenchymal transition (EMT), for example in embryogenesis, wound healing and cancer metastasis, when cells upregulate vimentin expression and downregulate keratin expression [4,[8][9][10]. We hypothesize that keratin and vimentin IFs have different mechanical properties already at the single filament level.…”
mentioning
confidence: 99%